DİABETİK RATLARDA LEVETİRASETAM VE GABAPENTİN AĞRI YANITLARININN HOT PLATE YÖNTEMİYLE KARŞILAŞTIRILMASI - BİNGÖL, ZEYNEP ATACAN (Fırat Üniveristesi, 2008)
Bu çalışmada streptozosin (STZ) ile indüklenmiş diabetik ratlarda, gabapentin (50-100 mg/kg) ve levetirasetamın (LEV, 54 mg/kg ve 170 mg/kg) farklı dozlarının hot plate ağrı eşiği düzeylerine etkileri araştırıldı.Kırk adet 3 haftalık beyaz wistar rat kullanıldı. Birinci grup 50 mg/kg gabapentin (n=7), ikinci grup 100 mg/kg gabapentin (n=7), üçüncü grup 54 mg/kg levetirasetam (n=7) ve dördüncü grup 170 mg/kg levetirasetam (n=7) uygulanan ratlardan oluşturuldu. Sadece STZ uygulanan beşinci grup (n=7) ve herhangi bir ilaç verilmeyen, içme suyu ve yemle beslenen altıncı grup (n=5) ise kontrol grupları olarak kabul edildi.Çalışma sonucunda, 100 mg/kg gabapentin kullanılan ikinci grupta ağrı eşiğinin, kontrol ve çalışma gruplarına göre anlamlı düzeyde arttığı gözlendi. 50 mg/kg gabapentin, 54 mg/kg ve 170 mg/kg levetirasetam uygulanan gruplarda da ağrı eşiği değerlerinde artış olmakla birlikte, kontrol grubu ile aralarındaki fark istatistiksel olarak anlamlılık düzeylerine ulaşmadı.Anahtar Kelimeler: diabetik nöropati, hot plate, gabapentin, levetirasetam

In this study, we have studied the effects of gabapentin (50 and 100 mg/kg) and levetiracetam (LEV,54 mg/kg and 170 mg/kg) in two different doses, on the pain treshold levels of diabetic rats induced with streptozosin.40 white wistar rats which are 3 weeks old were used in the study. In the first group there were rats on which 50 mg/kg gabapentin was administered (n=7); in the second group there were rats on which 100 mg/kg gabapentin was administered (n=7); in the third group there were rats on which 54 mg/kg levetiracetam was administered (n=7); in the forth group there were rats on which 170mg/kg levetiracetam was administered (n=7); in the fifth there were rats on which only STZ was administered (n=7) and in the sixth group (n=5) there were rats on which no drugs were administered but fed only with water and feed. The fifth and sixth groups are admitted as control groups.At the end of the experiment, it is obtained that the pain treshold in the second group on which 100 mg/kg gabapentin was administered is found meaningful increased comparison to the controls. Altough the groups on which 50 mg/kg gabapentin, 54 mg/kg ve 170 mg/kg levetiracetam administered are found increased pain treshold, but also any meaningful statistical difference is not found comparison to the control group.Key words: diabetic neuropathy, hot plate, gabapentin, levetiracetam
Comparison of pain responses to Levetiracetam and Gabapentine on diabetic rats by hot plate method
Keywords: Nöroloji